Tailoring of boron-doped MnTe semiconductor-sensitized TiO2photoelectrodes as near-infrared solar cell devices - Auttasit Tubtimtae (2018)
We studied the photovoltaic performance of a new tailoring of boron-doped MnTe semiconductor-sensitized solar cells (B-doped MnTe SSCs). The B-doped MnTe semiconductor was grown on TiO2using two-stages of the successive ionic layer adsorption and reaction (SILAR) technique as a photoelectrode. The phase of the boron-doped MnTe and MnTe2semiconductor as sensitizers were characterized with ∼20-50 nm in diameter. The B-doped MnTe(5) exhibited the best efficiency of 0.04%, compared to that of the undoped sample of 0.006%. In addition, the band gaps of 1.30 and 1.26 eV were determined for the undoped and B-doped MnTe NPs, respectively. The change in the band gap after boron doping was performed due to crystal quality improvement and the larger size of the MnTe NPs, leading to a broader absorption of the sensitizer and a noticeable improvement in the photovoltaic performance. This kind of semiconductor and synthesis procedure can be applied for further improvement in a higher efficiency and more stability in SSCs. © 2013 Published by Elsevier Ltd. All rights reserved.